The influence of protein restriction during mid- to late gestation on beef offspring growth, carcass characteristic and meat quality - Maresca, Sebastian; Lopez Valiente, Sebastian; Rodriguez, Alejandro Martin; Testa, Maria Laura; Long, Nathan M.; Quintans, Graciela I.; Pavan, Enrique (Elsevier, 2019)
The objective of this study was to determine whether crude protein intake during the last three months of gestation affects growth performance, carcass characteristics and meat quality of steer progeny. At 134 ± 14 d of gestation, 68 multiparous Angus cows were blocked by BW and expected calving date and randomly assigned to diets that contained either low or high dietary crude protein concentrations and were allotted in 12 pens per treatment. After calving, cows were managed together on improved pastures during lactation. After weaning at 219 ± 13 d of age, steers calves were stockered on natural pastures until 687 ± 13 d of age then placed into a feedlot for 83d before slaughter. Maternal dietary protein concentration had no influence on offspring body weight and growth rate during rearing or finishing phases (P > .10). Rib fat thickness of steers was not affected (P = .38) by maternal nutrition treatments, however, LM area was greater in HP steers than LP steers at entrance into the feedlot (P = .01) and end of finishing phase (P = .04). Hot carcass weight was similar between treatments (P = .69), however dressing percentage was increased in HP relative to LP steers (P = .01). Tenderness of Longissimus muscle was increased in HP compared to LP steers after 3 and 14d (P < .001) of aging. No treatment differences in troponin-t degradation (P = .77) and collagen content (P = .58) were observed. Muscle fiber diameter was similar in LP and HP steers (P = .20), suggesting that increase of LM area in HP steers could be due to muscle hyperplasia. These data indicated that level of protein during mid to late gestation does not affect offspring growth but has impacts on carcass composition and meat quality of steer progeny.